Biodistribution and radiation dosimetry in cancer patients of the ascorbic acid analogue 6-Deoxy-6-[18F] fluoro-L-ascorbic acid PET imaging: first-in-human study - Long, Yali; Yi, Chang; Wu, Renbo; Zhang, Yuying; Zhang, Bing; Shi, Xinchong; Zhang, Xiangsong; Zha, Zhihao (European journal of nuclear medicine and molecular imaging, 2023)
Purpose Clinical studies on the use of ascorbic acid (AA) have become a hot spot in cancer research. There remains an unmet need to assess AA utilization in normal tissues and tumors. 6-Deoxy-6-[ 18 F]fluoro-L-ascorbic acid ([ 18 F]DFA) displayed distinctive tumor localization and similar distribution as AA in mice. In this study, to evaluate the distribution, tumor detecting ability and radiation dosimetry of [ 18 F]DFA in humans, we performed the first-in-human PET imaging study. Methods Six patients with a variety of cancers underwent whole-body PET/CT scans after injection of 313–634 MBq of [ 18 F]DFA. Five sequential dynamic emission scans in each patient were acquired at 5–60 min. Regions of interest (ROI) were delineated along the edge of the source-organ and tumor on the transverse PET slice. Tumor-to-background ratio (TBR) was obtained using the tumor SUVmax to background SUVmean. Organ residence times were calculated via time-activity curves, and human absorbed doses were estimated from organ residence time using the medical internal radiation dosimetry method. Results [ 18 F]DFA was well tolerated in all subjects without serious adverse event. The high uptake was found in the liver, adrenal glands, kidneys, choroid plexus, and pituitary gland. [ 18 F]DFA accumulated in tumor rapidly and the TBR increased over time. The average SUVmax of [ 18 F]DFA in tumor lesions was 6.94 ± 3.92 (range 1.62–22.85, median 5.94). The organs with the highest absorbed doses were the liver, spleen, adrenal glands, and kidneys. The mean effective dose was estimated to be 1.68 ± 0.36 E −02 mSv/MBq. Conclusions [ 18 F]DFA is safe to be used in humans. It showed a similar distribution pattern as AA, and displayed high uptake and retention in tumors with appropriate kinetics. [ 18 F]DFA might be a promising radiopharmaceutical in identifying tumors with high affinity for SVCT2 and monitoring AA distribution in both normal tissues and tumors. Trial registration Chinese Clinical Trial Registry; Registered Number: ChiCTR2200057842 (registered 19 March 2022).